High-performance wide bandgap perovskite solar cells fabricated in ambient high-humidity conditions. Issue 19 (8th September 2021) - Menda, Ugur Deneb; Ribeiro, Guilherme; Nunes, Daniela; Calmeiro, Tomás; Águas, Hugo; Fortunato, Elvira; Martins, Rodrigo; Mendes, Manuel J.
Abstract : Low cost wide-bandgap perovskite solar cells (PSCs) fabricated in ambient air (relative humidity ∼70%) with a PCE of 16.4% with long term stability. Abstract : Lead-halide perovskite solar cells (PSCs) are currently the most promising emergent thin-film photovoltaic technology, having already reached power conversion efficiency (PCE) levels of state-of-the-art wafer-based silicon cells. The class of wide bandgap PSCs has also demonstrated high PCE values, thus becoming highly attractive for top sub-cells in tandem devices constructed with silicon or other types of bottom sub-cells. In this study, wide bandgap double-halide (Cs0.17 FA0.83 PbI3− x Br x ) perovskite absorbers were developed with different bromine content, aiming to obtain bandgap values between 1.66 to 1.74 eV, by a glovebox-free (ambient) procedure. Low-cost inorganic materials, i.e. TiO2 and CuSCN, were used for the electron and hole transport layers, respectively. The 1.70 eV bandgap perovskite resulted in the highest reproducibility and stability (>80% initial PCE after 3500 hours) properties of the PSCs, remarkably attaining 16.4% PCE even with ambient and high humidity (∼70%) fabrication conditions.